AUTOMORPHISMS OF FREE BURNSIDE GROUPS OF PERIOD 3 - Grigoryan, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
We have proved that any automorphism of the free Burnside group B(3) of period 3 and an arbitrary rank is induced by an automorphism of the free group of the same rank.